The Morphological Impact of Restructuring Routes: Atatürk Boulevard's Palimpsest Phenomenon - Güllü Bozdoğan; Tan Kamil Gürer (Alanya Üniversitesi, 2024)
Restructuring routes are significant urban elements that lead to physical changes in cities to meet modern needs, often resulting in traumatic transformations. This study investigates the morphological impact of the palimpsest phenomenon on Istanbul's Atatürk Boulevard, an exemplar of restructuring routes. The Boulevard's construction disrupted the organic urban fabric, creating a new structure and altering the area's identity. By employing a typomorphological analysis based on Conzen’s Town Plan Analysis, this research examines changes in the street, building, and subdivision systems. The study utilizes historical and contemporary maps to reveal the effects of Atatürk Boulevard on urban morphology, demonstrating both positive and negative consequences of restructuring routes. Findings indicate that the boulevard increased the economic value of the area but also led to the fragmentation and loss of historical urban elements, contributing to a complex urban palimpsest. The study highlights the need for sensitive urban planning to preserve the city's historical identity while accommodating modern developments. The insights gained are crucial for architects and urban planners in managing urban landscapes, ensuring sustainability, and respecting historical contexts in future developments